Immune‐related adverse events are associated with improved response, progression‐free survival, and overall survival for patients with head and neck cancer receiving immune checkpoint inhibitors. Issue 24 (21st September 2021) - Foster, Corey C.; Couey, Marcus A.; Kochanny, Sara E.; Khattri, Arun; Acharya, Rajesh K.; Tan, Yi‐Hung Carol; Brisson, Ryan J.; Leidner, Rom S.; Seiwert, Tanguy Y.
Abstract : Background: The authors hypothesized that patients developing immune‐related adverse events (irAEs) while receiving immune checkpoint inhibition (ICI) for recurrent/metastatic head and neck cancer (HNC) would have improved oncologic outcomes. Methods: Patients with recurrent/metastatic HNC received ICI at 2 centers. Univariate and multivariate logistic regression, Kaplan‐Meier methods, and Cox proportional hazards regression were used to associate the irAE status with the overall response rate (ORR), progression‐free survival (PFS), and overall survival (OS) in cohort 1 (n = 108). These outcomes were also analyzed in an independent cohort of patients receiving ICI (cohort 2; 47 evaluable for irAEs). Results: The median follow‐up was 8.4 months for patients treated in cohort 1. Sixty irAEs occurred in 49 of 108 patients with 5 grade 3 or higher irAEs (10.2%). ORR was higher for irAE+ patients (30.6%) in comparison with irAE− patients (12.3%; P = .02). The median PFS was 6.9 months for irAE+ patients and 2.1 months for irAE− patients ( P = .0004), and the median OS was 12.5 and 6.8 months, respectively ( P = .007). Experiencing 1 or more irAEs remained associated with ORR ( P = .03), PFS ( P = .003), and OS ( P = .004) in multivariate analyses. The association between development of irAEs and prolonged OS persisted in a 22‐week landmark analysis ( P = .049). The association between development of irAEs and favorable outcomes was verified in cohort 2. ConclusionS: The development of irAEs was strongly associated with an ICI benefit, including overall response, PFS, and OS, in 2 separate cohorts of patients with recurrent/metastatic HNC. Abstract : In this retrospective analysis of patients with metastatic head and neck cancer receiving immune checkpoint inhibition, the association between the development of immune‐related adverse events and outcomes is investigated. Developing immune‐related adverse events is strongly associated with clinical benefits, including overall response, progression‐free survival, and overall survival, in 2 separate cohorts of patients.